Para além do sonho e da vigilia. O sonho ameríndio e a existência - Orobitg, Gemma (Revista de Antropologia, 2022)
In this article, I analyze the double dimension of the Amerindian dream, as a journey of the soul and as an action caused by beings other than the dreamer. The objective is to discuss some recurring interpretations of the Amerindian dream and to explore the ontological status of the dream to outline an alternative proposal to those analyzes of the indigenous dream experience that reproduce the dream-wake dichotomy. Ethnographic studies on the Amerindian dream and my research among the Pumé indigenous people of the Llanos of southwestern Venezuela are the basis for answering the questions: what is to dream from the experience of the indigenous person? What the dream means? Why is the dream an ontological state, that is, it represents, on the one hand, the principle of vitality of the person and, on the other hand, the foundation of the existence of all the entities that populate the cosmos?